Etanercept protects ovarian reserve against ischemia/reperfusion injury in a rat model - KAYA, ÖZLEM TUĞÇE (TERMEDIA PUBLISHING HOUSE LTD, 2019)
Introduction: Etanercept has been widely used in autoimmune diseases for blocking tumor necrosis factor alpha (TNF-alpha), which is an inflammatory cytokine. The anti-apoptotic and anti-inflammatory effects of etanercept against ischemia/reperfusion (I/R) injury have been shown for several tissues in rat studies, but to the best of our knowledge, there are no reports on its protective effects following similar injury in ovarian tissue. The aim of this study was to investigate whether etanercept has beneficial effects on ovarian I/R injury, as well as on ovarian reserve. Material and methods: Twenty-four rats were randomly divided into four groups (n = 6/group): sham (laparotomy only); sham + etanercept; I/R; and I/R + etanercept. Ischemia was induced for 3 h by twisting the ovary, and 24 h after detorsion the ovarian tissues were collected to evaluate histopathologic changes, glutathione (GSH), malondialdehyde (MDA), myeloperoxidase (MPO), and superoxide dismutase (SOD) concentrations for oxidative stress, 8-hydroxy-2'-deoxyguanosine (8-OHdG) for DNA damage, caspase-3 activity for apoptosis and ovarian follicle counts. To measure anti-Mullerian hormone (AMH), serum samples were drawn before and after surgery. Results: Tissue GSH and SOD levels were significantly higher, while MDA and MPO levels were significantly lower in the I/R + etanercept group than in the I/R group (p < 0.05, p < 0.01, respectively). Tissue 8-OHdG and caspase-3 activity were significantly lower in the I/R+etanercept group than in the I/R group (p < 0.05, p < 0.01, respectively). Preoperative and postoperative AMH levels were compared and there was a significant reduction in the I/R and I/R + etanercept groups (p < 0.001, p < 0.001). The reduction of AMH in the I/R + etanercept group was significantly lower than in the I/R group. The primordial, preantral and small antral follicle numbers were also significantly higher in the I/R + etanercept group compared to the I/R group (p < 0.001, p < 0.001, p < 0.005, respectively). Conclusions: Etanercept attenuated inflammation and related oxidative stress and also helped to preserve ovarian reserve following ovarian I/R damage.
Keywords: apoptosis; etanercept; inflammation; ischemia/reperfusion injury; oxidative injury; ovary; ANTI-MULLERIAN HORMONE; ISCHEMIA-REPERFUSION; TORSION; DETORSION; ATORVASTATIN; INHIBITION; THERAPY; DAMAGE